ANALYSIS OF ACCIDENT-PRONE LOCATIONS AND ROAD SAFETY INSPECTIONS IN YOGYAKARTA CITY - Andini Kharisma Firdausi; Dwijoko Ansusanto (DEARSIP : Journal of Architecture and Civil, 2025)
The growth in the number of motor vehicles and community activities in Yogyakarta City put great pressure on the transportation system, which has an impact on the increasing number of traffic accidents. The high accident rate shows the need to identify vulnerable locations as a basis for the preparation of prevention strategies. This study aims to identify accident-prone locations in the city of Yogyakarta through a spatial approach and formulate handling recommendations based on the results of road safety inspections. The methods used include spatial analysis using the ArcMap software-based Geographic Information System (GIS), with three main approaches, namely spatial autocorrelation analysis (Moran's I), hotspot analysis (Getis-Ord Gi), and density estimation (Kernel Density Estimation). Accident data was obtained from the Yogyakarta City Resort Police and weighted using the Equivalent Accident Number (EAN) method. The results of the analysis identified 16 hotspot points with a 99% confidence level, as well as four priority locations that require immediate handling, namely Jalan Kyai Mojo, Jalan Menteri Supeno, Jalan P. Diponegoro, and Jalan Brigjen Katamso. The results of road safety inspections show that there are problems such as damage to the road surface, markings that are not clearly visible, lack of traffic signs, and misuse of sidewalks. Handling recommendations include repairing road infrastructure, repainting markings, adding signs and crossing facilities, and restoring sidewalk functions for pedestrians. It is hoped that the implementation of this recommendation can reduce the accident rate and significantly improve traffic safety in the city of Yogyakarta.